Introduction to Libstats - Whitehair, Kristin; Theiss-White, Danielle; Coleman, Jason; Askey, Dale (My University, 2008)
Presentation from a workshop for the Kansas City Metropolitan Library Information Network (KCMLIN) on April 1, 2008. Workshop facilitators included Kristin Whitehair, Danielle Theiss-White, Jason Coleman, and Dale Askey.
Keywords: Libstats; Reference tracking system; Web-based tracking system; Library statistics; Reference services management